Botanical day to day: A playful proposal for teaching science - Horsth, Lucinea Carolina; Holanda Righetti de Abreu, Vanessa; Felipe Silva Gonçalves , Agda; Teodoro dos Reis , Lavinia (Guará Journal, 2025)
The development and use of teaching materials to meet the educational demands of new generations is becoming increasing complex. This is due to the fact that the development and use of these materials requires time, adequate training for professionals and the application of diversified methods that cater for all students. Therefore, the aim of this study was to highlight the connections between everyday productsand objects of plant origin and their relationship with the environment, considering four essential materials of human life, which are also present in the classroom: wood, paper, tissue and food. The material developed was aimed at primary school students and can be used both by students in Specialized Educational Assistance (AEE) and in the ordinary classroom, regardless of whether or not they have special educational needs. The results show that we are encouraging people to learn Botany and that, by providing active educators with access to university extension projects and support and knowledge about new teaching methodologies, we are facilitating integration between initial and continuing training, as well as opening up opportunities for teachers to update their knowledge.
Keywords: Inclusive education; University Extension; Pedagogical games